PENGARUH PENDEKATAN MATEMATIKA REALISTIK BERBANTUAN GEOGEBRA TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP NEGERI 27 MEDAN - Nurul Indah Klismei Agung; Kairuddin Kairuddin (De Fermat : Jurnal Pendidikan Matematika, 2026)
This study aimed to determine the effect of the Realistic Mathematics Approach assisted by Geogebra on the mathematical problem-solving ability of eighth-grade students at SMP Negeri 27 Medan and to describe students’ answer processes in solving mathematical problems. This research used a pre-experimental method with a one group pre-test-post-test design. The population consisted of all eighth-grade students of SMP Negeri 27 Medan, with one experimental class selected through cluster random sampling. Data were collected through mathematical problem-solving ability tests. The results showed that the average pre-test score of 48.66 increased to 81.83 in the post-test. The data were normally distributed and homogeneous. Hypothesis testing showed a significance value of 0.000 < 0.05, indicating a significant effect of the Realistic Mathematics Approach assisted by Geogebra on students’ mathematical problem-solving ability. The coefficient of determination (R-Square) was 0.663, indicating a contribution of 66.3%. Students’ answer processes showed that students were able to understand problems, plan solutions, carry out solutions, and recheck the obtained results.